2020
DOI: 10.3389/fnins.2020.00596
|View full text |Cite
|
Sign up to set email alerts
|

Pinpointing Neural Correlates of Attachment in Poly-Drug Use: A Diffusion Tensor Imaging Study

Abstract: An increasing amount of evidence indicates the significance of attachment in the etiology of poly-drug use disorder (PUD). The aim of this study was to investigate associations between PUD and adult attachment in particular, with a focus on white matter (WM) fiber tract integrity. For this purpose, we selected several regions-ofinterest based on previous findings which were examined for their role in PUD and estimated whole-brain associations between adult attachment and WM integrity. A total sample of 144 rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…This shortcoming needs to be addressed in future studies. What is more, a recent study by Fuchshuber et al (74) indicated a medium effect size regarding the difference in attachment security comparing PUD and HC groups (74). With respect to the relatively small sample size employed in this study, future research addressing this subject might take this to an account regarding the estimation of the required sample size.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 75%
“…This shortcoming needs to be addressed in future studies. What is more, a recent study by Fuchshuber et al (74) indicated a medium effect size regarding the difference in attachment security comparing PUD and HC groups (74). With respect to the relatively small sample size employed in this study, future research addressing this subject might take this to an account regarding the estimation of the required sample size.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 75%